Optimization of dye-sensitized solar cells with poly(1-vinylpyrrolidone-co-vinyl acetate) gel polymer electrolytes containing binary salts and ionic liquid / Ng Hon Ming - Ng, Hon Ming (2016)
Energy requirement has become a popular topic in almost every nation around the world. Instead of burning the depleting conventional fossils fuels as the source of energy, researchers nowadays are focusing more on developing more reliable renewable energy resources. Solar energy is one of the interesting renewable energy technology which could easily be the best choice to deal with the growing energy demand. This is because the sun energy is so abundant that it could be literally obtained anywhere on our earth. One of the promising technologies invented for the solar harvesting applications is the dye sensitized solar cells (DSSCs). These cells have the ability to surpass the leading types of solar cells which are based on silicon with a number of unique advantages that the DSSCs have. However, most of the high performance DSSCs are fabricated with liquid electrolytes and these types of DSSCs face complications in long term practical use due to the potential possibility of evaporation, leakage, desorption, photodegradation of the dye, corrosion of the platinum secondary electrode and ineffective sealing of cells. Thus, in order to overcome these drawbacks, gel polymer electrolytes (GPE) have emerged as great alternatives to replace the liquid electrolytes. Unfortunately, even with some advantages over the liquid electrolytes, GPEs are still facing serious problems on low power conversion efficiencies and poor ionic conductivity. Thus, in order to overcome these problems, we have taken several strategies to improve the ionic conductivity as well as the photovoltaic performance of these GPE-based DSSCs. In this study, we assembled dye sensitized solar cells (DSSCs) with poly(1-vinylpyrrolidone-co-vinyl acetate) (P(VP-co-VAc)) co-polymer based gel polymer electrolytes as the usage of co-polymer could increase the stability window of the GPE due to the nature of co-polymer having both amorphous phase and the crystalline phase. We also incorporate these GPEs with two types of the different salts (potassium iodide [KI] and tetrapropylammonium iodide [TPAI]) with different size in different concentration to improve the GPE for the DSSCs. v Then, 1-methyl-3-propylimidazolium iodide (MPII) ionic liquid was added in into the best binary salt system sample. Fourier transform infrared (FTIR) studies confirmed the complexation of the P(VP-co-VAc)-based gel polymer electrolytes. The effects of the incorporation of the binary salt and ionic liquid were studied. The binary salt system samples were able to achieve highest ionic conductivity and power conversion efficiency of 1.90 × 10-3 S cm-1 and 5.53%, respectively. Interestingly, upon the addition of the ionic liquid, MPII into this sample the ionic conductivity and the power conversion efficiency had increased to 4.09 × 10-3 S cm-1 and 5.94%, respectively at its optimum concentration. In order to learn more about the GPEs and DSSCs, the dielectric and electric dispersion behaviors of the GPEs were studied by dielectric relaxation spectroscopy at ambient temperature and the electrochemical impedance studies of the DSSCs were conducted. The electrocatalytic activity of the DSSC has also been investigated using Tafel polarization studies.